Polymorphisms of the apolipoprotein E gene affect response to atorvastatin therapy in acute ischemic stroke - Bi, QianQian; Zhou, XiaoYu; Lu, YanQin; Fu, Wang; Wang, YongPeng; Wang, Feng; Wang, Jue (Frontiers in Cardiovascular Medicine, 2022)
Background: Polymorphisms of the apolipoprotein E (APOE) gene are related to the effects of statins. The biological functions of APOE subtypes determine the metabolism of blood plasma lipids and the progression of atherosclerosis. This study aimed to explore the impact of APOE gene polymorphisms on the effect of atorvastatin on lipid regulation and plaque stabilization. Methods: It was a prospective cohort study. We consecutively enrolled patients with acute ischemic stroke in the Department of Neurology, Shanghai Tenth People's Hospital, from December 2018 to December 2019. The patients were divided into E2, E3, and E4 groups according to their APOE genotype. 20 mg atorvastatin was administrated in all enrolled patients. The changes in the levels of blood lipids over three months, the size and stability of plaques over 12 months were analyzed. Results: We enrolled 253 consecutive patients with acute ischemic stroke, and 136 had carotid atherosclerotic plaque. Two patients with genotype E2/E4 were excluded. There were 30 subjects in the E2 group (12.0%), 191 subjects in the E3 group (76.0%), and 30 subjects in the E4 group (12.0%). The lowest reduction percentage in low-density lipoprotein cholesterol (LDL-C) was observed in group E4 (41.2%), while the highest reduction percentage was observed in group E2 (17.6%). The length of the plaques grew slower in the E2 group and faster in the E4 group. Conclusion: APOE gene polymorphisms affect the biological functions of atorvastatin. The ε2 allele had a better lipid-lowering effect on LDL-C, enhanced the ability of atorvastatin to stabilize carotid artery plaques, and slowed the progression of the length of carotid artery plaques compared to the ε3 or ε4 allele.